"Fighers for the Freedom of Ukraine" : Canada's Nazi Collaborator Monuments - Rudling, Per Anders (Routledge Studies in Fascism and the Far Right, 2025)
The 14th Waffen-SS Division Galizien was set up in 1943 by Ukrainian volunteers, largely sympathetic to the more conservative Melnyk wing of the Organization of Ukrainian Nationalists (OUN(m)). Its members took a personal oath of allegiance to Adolf Hitler and served in a number of capacities on the eastern front. In addition to combat at the front, the unit partook in the crushing of the Slovak National Uprising in 1944, and counterinsurgency campaigns against Yugoslav partisans in Slovenia. After the war, the veterans settled across the world, but were concentrated largely in Canada and the United Kingdom (UK). The veterans erected a number of monuments to their unit, as freedom fighters who died for the liberty of Ukraine. These became meeting points where the veterans and their followers gathered to commemorate fallen comrades and to reiterate their narration of history. How did the veterans represent their past to the host societies, most of which having been on the allied side, fighting the Nazis? Why were monuments to Waffen-SS and other collaborators were regarded as unexceptional when constructed, and why have they generated attention and controversy now, 80 years after the end of World War II, when virtually all veterans have passed? Through a study of the memorials, this chapter seeks to analyze the memory culture of the Ukrainian diaspora far-right.
Keywords: Ukraine; Waffen-SS Galizien; OUN; Roman Shukhevych; Multiculturalism; Canada; Identity politics; Holocaust; Ukrainian Canadian Congress